Non-aqueous electrolyte and lithium ion battery thereof

By using a nonaqueous electrolyte in a lithium-ion battery, including compounds of Structural Formula I and Structural Formula II, the thermal stability problem of lithium cobalt oxide-based lithium-ion batteries in high temperature environments is solved, and the high-temperature storage, circulation performance and normal temperature circulation performance of the battery are significantly improved.

CN119627229APending Publication Date: 2025-03-14ZHUHAI SMOOTHWAY ELECTRONICS MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964563.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Lithium cobalt oxide lithium-ion batteries have poor thermal stability in high temperature environments, which can easily lead to a decrease in battery capacity and electrode polarization, thereby reducing electrochemical performance and increasing the risk of explosion.

Method used

A nonaqueous electrolyte is used, including lithium salts, nonaqueous organic solvents and specific additives, including compounds of Structural Formula I and Structural Formula II. The cyclic unsaturated sulfonimide salt structure of structural formula I polymerizes at the interface between positive and negative electrodes to form a protective layer (SEI layer), while the fluorosulfonamide structure of structural formula II coordinates to regulate the SEI structure to improve the high temperature stability of the battery.

Benefits of technology

By collaborating with the compounds of Structural Formula I and Structural Formula II, the internal resistance of the lithium-ion battery is significantly reduced, its high-temperature storage, circulation performance and normal temperature circulation performance are improved, and the overall electrochemical performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627229A_ABST
    Figure CN119627229A_ABST
Patent Text Reader

Abstract

The invention provides a non-aqueous electrolyte and a lithium ion battery thereof. The non-aqueous electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, and the additive comprises compounds as shown in a structural formula I and a structural formula II. Wherein M is selected from alkali metal, R is selected from hydrogen atoms or hydrocarbyl with the carbon atom number of 1-6, R1 and R2 are independently selected from hydrocarbyl with the carbon atom number of 1-6 and halogenated hydrocarbyl with the carbon atom number of 1-6, or R1 and R2 are combined with each other to form a cyclic structure. The non-aqueous electrolyte contains the compounds shown in the structural formula I and the structural formula II, so that the internal resistance of the battery can be effectively reduced and the high-temperature storage performance, the high-temperature cycle performance and the normal-temperature cycle performance of the battery can be improved through the synergistic cooperation of the compounds shown in the structural formula I and the structural formula II. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery thereof. Background Art

[0002] In recent years, with the rapid growth of the new energy vehicle market and the explosive growth of the energy storage market, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and large energy storage systems due to their high energy density, long cycle life and wide operating temperature range. With the advancement of technology, people's requirements for the performance of lithium-ion batteries are also constantly increasing.

[0003] Lithium cobalt oxide lithium-ion battery is a high-performance lithium-ion battery. During the charge and discharge process, lithium ions move back and forth between the positive and negative electrodes to store and release electrical energy. During charging, positively charged lithium ions escape from the positive electrode LiCoO2 crystal cells, pass through the diaphragm, reach the negative electrode, and react with the negative electrode carbon to generate Li x C6 is embedded in the negative electrode; during discharge, lithium ions fall off from the negative electrode and reach the positive electrode, reacting with the positive electrode charging reaction product Li 1-x CoO2 reacts to regenerate LiCoO2. Lithium cobalt oxide lithium-ion batteries are widely used in mobile phones, computers, electric vehicles, drones and other fields due to their advantages such as high first discharge specific capacity, energy density and long cycle life. However, lithium cobalt oxide lithium-ion batteries have poor thermal stability and are easily decomposed into lithium oxide, cobalt oxide and oxygen in high temperature environments, which in turn causes the battery capacity to decrease, leading to electrode polarization, which reduces the overall electrochemical performance of the battery and even creates the risk of explosion. At present, you can choose to optimize the electrolyte components and use additives to improve the high temperature performance of lithium cobalt oxide lithium-ion batteries. Among them, the use of additives is a more effective way to improve. Therefore, the continuous development of new electrolyte additives to improve the high temperature performance of lithium cobalt oxide lithium-ion batteries is extremely important to adapt to the development of technology. Summary of the invention

[0004] The object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery thereof. The non-aqueous electrolyte of the present invention can effectively reduce the internal resistance of the battery and improve the high-temperature storage, high-temperature cycle performance and room-temperature cycle performance of the battery.

[0005] To achieve the above object, the present invention provides a non-aqueous electrolyte, including a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive includes a compound represented by structural formula I and structural formula II:

[0006]

[0007] Among them, M is selected from alkali metals, R is selected from hydrogen atom or hydrocarbon group with carbon number 1 to 6, R1 and R2 are each independently selected from hydrocarbon group with carbon number 1 to 6, halogenated hydrocarbon group with carbon number 1 to 6, or R1 and R2 are combined to form a ring structure.

[0008] Compared with the prior art, the non-aqueous electrolyte of the present invention contains additive compounds of structural formula I and structural formula II, wherein structural formula I is a cyclic unsaturated sulfonyl imide salt structure, which can polymerize at the positive and negative electrode interfaces to form an SEI layer to improve the battery's cycle performance and high-temperature storage performance, but it may decompose at high temperatures and react adversely with other components in the non-aqueous electrolyte, resulting in an increase in the battery's internal resistance, which makes it more limited in improving the battery's cycle performance and high-temperature storage performance. The addition of the fluorosulfonamide structure shown in structural formula II, first, can coordinate with the compound of structural formula I to regulate the SEI constituent components, increase the content of inorganic components such as lithium fluoride, reduce the internal resistance of lithium-ion batteries, and improve the overall electrochemical performance of the battery. Secondly, in a high temperature environment, the fluorosulfonamide structure shown in structural formula II helps maintain the stability of the non-aqueous electrolyte and the stability of the electrode / electrolyte interface. By inhibiting the decomposition of the non-aqueous electrolyte and the occurrence of adverse reactions, the battery's cycle performance and storage performance under high temperature conditions can be significantly improved. Therefore, the present invention can effectively reduce the internal resistance of the battery and improve the high-temperature storage, high-temperature cycle performance and room-temperature cycle performance of the battery through the synergistic combination of the compound of structural formula I and the compound of structural formula II.

[0009] Preferably, M is selected from lithium, sodium, potassium, rubidium, cesium, R is selected from a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, R1 and R2 are each independently selected from an alkyl group having 1 to 3 carbon atoms, a fluoroalkyl group having 1 to 3 carbon atoms, or R1 and R2 are combined to form a cycloalkane.

[0010] Preferably, the compound represented by structural formula I is at least one selected from compound 1 to compound 5:

[0011]

[0012] Specifically, compounds 1 to 5 can be synthesized according to the following route:

[0013]

[0014]

[0015] Preferably, the compound represented by structural formula II is at least one selected from compound 6 to compound 10:

[0016]

[0017]

[0018] Preferably, the mass percentage of the compound represented by structural formula I in the non-aqueous electrolyte is 0.05% to 5%, and the mass percentage of the compound represented by structural formula II in the non-aqueous electrolyte is 0.05% to 5%.

[0019] Specifically, the mass percentage of the compound represented by structural formula I in the non-aqueous electrolyte may be, but is not limited to, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. The mass percentage of the compound represented by structural formula II in the non-aqueous electrolyte may be, but is not limited to, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%.

[0020] Preferably, the mass percentage of the compound represented by structural formula I in the non-aqueous electrolyte is 0.1% to 2%, and the mass percentage of the compound represented by structural formula II in the non-aqueous electrolyte is 0.1% to 4%.

[0021] Preferably, the mass percentage of the compound represented by structural formula I in the non-aqueous electrolyte is 0.1% to 1%, and the mass percentage of the compound represented by structural formula II in the non-aqueous electrolyte is 0.5% to 2%.

[0022] Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium difluorophosphate (LiPO2F2), lithium fluorosulfonate (LiSO3F), lithium bisoxalate borate (LiBOB), lithium difluorooxalate borate (C2BF2LiO4), lower aliphatic lithium carboxylate, lithium difluorobisoxalate phosphate (LiDFBP) and lithium bisfluorosulfonyl imide (LiFSI). In some technical solutions, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), and in some technical solutions, the lithium salt is selected from a mixture of lithium hexafluorophosphate (LiPF6) and lithium bisoxalate borate (LiBOB).

[0023] Preferably, the mass percentage of the lithium salt in the non-aqueous electrolyte is 5% to 25%.

[0024] Specifically, the mass percentage of lithium salt in the non-aqueous electrolyte can be, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18%, 20%. Preferably, the mass percentage of lithium salt in the non-aqueous electrolyte is 8% to 20%, and more preferably, the mass percentage of lithium salt in the non-aqueous electrolyte is 10% to 15%.

[0025] Preferably, the non-aqueous organic solvent is at least one selected from the group consisting of linear carbonates, cyclic carbonates and carboxylates.

[0026] Specifically, the non-aqueous organic solvent can be selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), butyl acetate (n-Ba), γ-butyrolactone (γ-Bt), propyl propionate (n-Pp), ethyl propionate (EP) and ethyl butyrate (Eb).

[0027] Another aspect of the present invention provides a lithium-ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the electrolyte is the aforementioned non-aqueous electrolyte.

[0028] Preferably, the positive electrode material is selected from lithium cobalt oxide material.

[0029] Specifically, the lithium cobalt oxide material may be lithium cobalt oxide (LiCoO2) or lithium cobalt oxide modified by doping and coating.

[0030] Preferably, the negative electrode material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon-carbon composite material and silicon monoxide.

[0031] Specifically, the negative electrode material is selected from artificial graphite. DETAILED DESCRIPTION

[0032] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0033] Example 1

[0034] (1) Preparation of non-aqueous electrolyte

[0035] In an argon atmosphere, in a vacuum glove box with a moisture content of <1ppm, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a weight ratio of EC:EMC=3:7 to obtain 86.7g of a non-aqueous organic solvent, followed by adding 0.3g of compound 1 and 0.5g of compound 6 additives, dissolving and stirring thoroughly, then adding LiPF6 and mixing evenly to obtain a non-aqueous electrolyte.

[0036] (2) Preparation of positive electrode

[0037] Lithium cobalt oxide (LiCoO2), adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 98:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of the aluminum foil, dried and rolled to obtain a positive electrode sheet.

[0038] (3) Preparation of negative electrode

[0039] Artificial graphite, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 90:2:8 to prepare a lithium secondary battery negative electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of a copper foil, and then dried and rolled to obtain a negative electrode sheet.

[0040] (4) Preparation of lithium-ion batteries

[0041] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, and then stacked as needed. After the tabs are welded, they are placed in the aluminum plastic film of the battery outer packaging, and the prepared non-aqueous electrolyte is injected into the dried bare battery cell, and vacuum packaging, standing, formation (first charged to 3.5V at 0.2C constant current, then charged to 3.8V at 0.3C constant current, and finally charged to 4.5V at 1C constant current), shaping, capacity testing and other processes are carried out successively, and finally a 1Ah soft-pack lithium secondary battery is obtained.

[0042] The non-aqueous electrolyte formulations of Examples 1 to 16 and Comparative Examples 1 to 3 are shown in Table 1, wherein the electrolyte preparation and battery preparation steps of Examples 2 to 16 and Comparative Examples 1 to 3 are the same as those of Example 1.

[0043] Table 1 Non-aqueous electrolyte formulations of Examples 1 to 16 and Comparative Examples 1 to 3

[0044]

[0045]

[0046] The lithium ion batteries prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were subjected to high temperature storage tests and normal temperature cycle tests, respectively. The specific test conditions are as follows. The performance test results are shown in Table 2.

[0047] Normal temperature cycle test

[0048] At room temperature (25°C), the lithium-ion battery is charged and discharged once at 1.0C / 1.0C (the battery discharge capacity is C0) with an upper limit voltage of 4.53V, and then charged and discharged at 1.0C / 1.0C for 500 cycles at room temperature (the battery discharge capacity is C1).

[0049] Capacity retention rate = (C1 / C0)*100%

[0050] Lithium-ion battery high temperature storage performance test

[0051] At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.2C / 0.2C (the battery discharge capacity is recorded as C0), and the upper limit voltage is 4.53V; the battery is placed in a 60°C oven for 30 days, the battery is taken out, and the battery is placed in a 25°C environment for 0.2C discharge, and the discharge capacity is recorded as C1; then the lithium-ion battery is charged and discharged at 0.2C / 0.2C (the battery discharge capacity is recorded as C2), and the capacity retention rate and capacity recovery rate of the lithium-ion battery are calculated using the following formula:

[0052] Capacity retention rate = (C1 / C0) · 100%

[0053] Capacity recovery rate = (C2 / C0) · 100%

[0054] Lithium-ion battery high temperature cycle performance test

[0055] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to make the lithium-ion battery reach a constant temperature. Charge it at a constant current of 4C to a voltage of 4.53V, then charge it at a constant voltage of 4.53V to a current of 0.05C, and then discharge it at a constant current of 4C to a voltage of 3.0V. Record the first discharge capacity of the battery as C0, which is a charge and discharge cycle. Then charge and discharge it at 1C / 1C for 1000 cycles at 45℃, record the discharge capacity as C1, and use the following formula to calculate the capacity retention rate of the lithium-ion battery.

[0056] Capacity retention rate = (C1 / C0) · 100%

[0057] Internal resistance test

[0058] Place the divided lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge at 1C constant current to a voltage of 4.53V, then charge at 4.53V constant voltage to a current of 0.05C, then discharge at 1C constant current to a voltage of 3.0V, and record the first discharge capacity of the battery as C0. This is a charge and discharge cycle. Then charge and discharge at 1C / 1C for 3 weeks at 25℃, and discharge to 0.5C0. Remove the battery to test the DC internal resistance R of the battery.

[0059] Table 2 Lithium ion battery performance test results of Examples 1 to 16 and Comparative Examples 1 to 3

[0060]

[0061]

[0062] It can be seen from the results in Table 2 that, compared with Comparative Example 1, the lithium ion batteries of Examples 1 to 16 have better high-temperature storage performance, high-temperature cycle performance and room-temperature cycle performance. This may be because the non-aqueous electrolyte of the present invention contains additive compounds of structural formula I and structural formula II, wherein structural formula I is a cyclic unsaturated sulfonyl imide salt structure, which can be polymerized at the positive and negative electrode interfaces to form an SEI layer to improve the battery's cycle performance and high-temperature storage performance, but it may decompose at high temperatures and react adversely with other components in the non-aqueous electrolyte, resulting in an increase in the battery's internal resistance, thereby limiting its improvement in the battery's cycle performance and high-temperature storage performance. The addition of the fluorosulfonamide structure shown in structural formula II, first, can coordinate with the compound of structural formula I to regulate the SEI components, increase the content of inorganic components such as lithium fluoride, reduce the internal resistance of the lithium ion battery, and improve the overall electrochemical performance of the battery. Secondly, under high temperature conditions, the fluorosulfonamide structure shown in structural formula II helps to maintain the stability of the non-aqueous electrolyte and the stability of the electrode / electrolyte interface. By inhibiting the decomposition of the non-aqueous electrolyte and the occurrence of adverse reactions, the cycle performance and storage performance of the battery under high temperature conditions can be significantly improved. Therefore, the present invention can effectively reduce the internal resistance of the battery and improve the high temperature storage, high temperature cycle performance and room temperature cycle performance of the battery through the synergistic combination of the compound of structural formula I and the compound of structural formula II.

[0063] Further comparison of the performance test results of Example 5 with those of Comparative Examples 2 to 3 shows that when only the compound of Structural Formula I or Structural Formula II is used, the improvement effect on the high temperature storage and cycle performance of the lithium ion battery is limited, and the improvement effect is lower than that of Example 5. This further confirms that the present invention can form a stable SEI film, reduce the internal resistance of the battery, and improve the high temperature storage performance, high temperature cycle performance, and room temperature cycle performance of the lithium ion battery only by adding the compounds shown in Structural Formula I and Structural Formula II to the lithium ion battery electrolyte at the same time.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, characterized in that: The additives include compounds shown in structural formula I and structural formula II: Among them, M is selected from alkali metals, R is selected from hydrogen atom or hydrocarbon group with carbon number 1 to 6, R1 and R2 are each independently selected from hydrocarbon group with carbon number 1 to 6, halogenated hydrocarbon group with carbon number 1 to 6, or R1 and R2 are combined to form a ring structure.

2. The non-aqueous electrolyte according to claim 1, characterized in that M is selected from lithium, sodium, potassium, rubidium, and cesium, R is selected from a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, R1 and R2 are each independently selected from an alkyl group having 1 to 3 carbon atoms, a halogenated alkyl group having 1 to 3 carbon atoms, or R1 and R2 can be combined with each other to form a cycloalkane.

3. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula I is selected from at least one of compounds 1 to 5:

4. The non-aqueous electrolyte according to claim 1, characterized in that The compound represented by the structural formula II is selected from at least one of compounds 6 to 10:

5. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound represented by the structural formula I in the non-aqueous electrolyte is 0.05% to 5%, and the mass percentage of the compound represented by the structural formula II in the non-aqueous electrolyte is 0.05% to 5%.

6. The non-aqueous electrolyte according to claim 5, characterized in that The mass percentage of the compound represented by the structural formula I in the non-aqueous electrolyte is 0.1% to 2%, and the mass percentage of the compound represented by the structural formula II in the non-aqueous electrolyte is 0.1% to 4%.

7. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium difluorophosphate, lithium fluorosulfonate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium lower aliphatic carboxylate, lithium difluorobisoxalatophosphate and lithium bisfluorosulfonyl imide.

8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is selected from at least one of chain carbonates, cyclic carbonates and carboxylates.

9. A lithium-ion battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The electrolyte is the non-aqueous electrolyte according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, characterized in that: The positive electrode material is selected from lithium cobalt oxide materials.